Faktor Predisposisi Yang Mempengaruhi Kelengkapan Imunisasi Dasar Polio Selama Masa Pandemi Covid-19 Di Wilayah Kerja Puskesmas Susunan Baru - Devi Ayu Wulandari; Astri Pinilih; Tusy Triwahyuni; Devita Febriani Putri (Universitas Malahayati Lampung, 2022)
ABSTRACT Polio immunization reported by WHO in 2016 that 85% of infants received 3 doses of Polio vaccine. Polio immunization is an immunization that is given so that a person gets defense against poliomyelitis. Three factors analyze human behavior from a health level, namely predisposing factors, supporting factors, and driving factors. To determine the predisposing factors that affect the completeness of basic Polio immunization during the COVID-19 pandemic in the work area of the Susunan Baru Health Center in 2021. This type of research uses descriptive analytic methods and uses a questionnaire on respondents who are mothers who have children aged 5-18 months. It is known that the frequency distribution of complete basic polio immunization is 58 people (81.7%). Variables that affect and have a relationship with the completeness of basic polio immunization at the Susunan Baru Health Center are mother's knowledge (p value = 0.000), mother's attitude (p value = 0.002, mother's education (p value = 0.042), and mother's occupation (p value = 0.016 The independent variable that most influences the completeness of basic polio immunization is the knowledge variable with an OR value of 10.329. Based on Spearman's correlation test, it was found that there was a relationship between knowledge, attitude, education, and occupation with completeness of basic Polio immunization, and based on logistic regression test the most influential variable with completeness of Polio immunization was knowledge variable. Keywords: Knowledge, Attitude, Education, Occupation, Polio Immunization ABSTRAK Imunisasi Polio dilaporkan WHO tahun 2016 sebesar 85% bayi mendapatkan 3 dosis vaksin Polio. Imunisasi Polio adalah imunisasi yang diberikan agar seseorang mendapat pertahanan terhadap penyakit Poliomyelitis.Tiga faktor yang menganalisa perilaku manusia dari tingkat kesehatan, yaitu faktor predisposisi,faktor pendukung, dan faktor pendorong. Tujuan penelitian ini untuk mengetahui faktor predisposisi yang mempegaruhi kelengkapan imunisasi dasar Polio selama masa pandemi COVID-19 di wilayah kerja Puskesmas Susunan Baru tahun 2021. Jenis penelitian ini menggunakan metode deskriptif analitik dan menggunakan kuesioner pada responden ibu yang memiliki anak usia 5-18 bulan. Diketahui distribusi frekuensi imunisasi dasar polio lengkap sebanyak 58 orang (81.7%). Variabel yang memengaruhi dan memiliki hubungan dengan kelengkapan imunisasi dasar Polio di Puskesmas Susunan Baru yaitu pengetahuan ibu (p value = 0,000), sikap ibu (p value =0.002, Pendidikan ibu (p value =0.042), dan pekerjaan ibu (p value =0.016). Variabel independen yang paling mempengaruhi kelengkapan imunisasi dasar Polio adalah variabel pengetahuan dengan nilai OR 10.329. Berdasarkan uji korelasi Spearman’s didapatkan ada hubungan antara pengetahuan,sikap,pendidikan, dan pekerjaan dengan kelengkapan imunisasi dasar Polio, dan berdasarkan uji regresi logistic variabel yang paling berpengaruh dengan kelengkapan imunisasi Polio adalah variabel pengetahuan. Kata Kunci: Pengetahuan, Sikap, Pendidikan, Pekerjaan, Imunisasi Polio